2023
DOI: 10.1038/s41467-023-40484-7
|View full text |Cite
|
Sign up to set email alerts
|

A sex-specific thermogenic neurocircuit induced by predator smell recruiting cholecystokinin neurons in the dorsomedial hypothalamus

Abstract: Olfactory cues are vital for prey animals like rodents to perceive and evade predators. Stress-induced hyperthermia, via brown adipose tissue (BAT) thermogenesis, boosts physical performance and facilitates escape. However, many aspects of this response, including thermogenic control and sex-specific effects, remain enigmatic. Our study unveils that the predator odor trimethylthiazoline (TMT) elicits BAT thermogenesis, suppresses feeding, and drives glucocorticoid release in female mice. Chemogenetic stimulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The neural basis for predator-induced hypophagia was recently shown to recruit CCK neurons found in the dorsal premammilary nucleus, which has activity that suppresses AgRP neurons ( 90 ). Remarkably, we also observed that DMH-CCK neurons contribute to stress-induced hypophagia, with their activation inhibiting feeding and their inhibition restoring normal food intake despite the presence of a predator odor ( 83 ). Interestingly, physical restraint selectively induced anorexigenic POMC neuron activity in ARC to suppress feeding, whereas other stressors, such as TMT, had no effect on POMC neuronal activation ( 91 ).…”
Section: Feedforward Mechanisms Affecting Energy Homeostasis: Predato...mentioning
confidence: 79%
See 2 more Smart Citations
“…The neural basis for predator-induced hypophagia was recently shown to recruit CCK neurons found in the dorsal premammilary nucleus, which has activity that suppresses AgRP neurons ( 90 ). Remarkably, we also observed that DMH-CCK neurons contribute to stress-induced hypophagia, with their activation inhibiting feeding and their inhibition restoring normal food intake despite the presence of a predator odor ( 83 ). Interestingly, physical restraint selectively induced anorexigenic POMC neuron activity in ARC to suppress feeding, whereas other stressors, such as TMT, had no effect on POMC neuronal activation ( 91 ).…”
Section: Feedforward Mechanisms Affecting Energy Homeostasis: Predato...mentioning
confidence: 79%
“…This rise in temperature likely serves to enhance both physical and neural performance by raising the temperature of muscles and the central nervous system by a few degrees Celsius. PSH represents an automatic stress reaction that activates the sympathetic nervous system, triggering a series of physiological responses and resulting in increased energy expenditure ( 83 ). Blockade of β3-adrenoreceptors efficiently reduces PSH, whereas cyclooxygenase inhibitors, which are used to decrease inflammation-induced fever, are ineffective ( 84 86 ).…”
Section: Feedforward Mechanisms Affecting Energy Homeostasis: Predato...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that after exposing mice to predator odors, there is a stress-induced hyperthermia and Fos expression in the MeA, DMH, LH, and ARC regions. Chemogenetic activation of the DMH neurons is sufficient to induce thermogenesis in females (Jovanovic, Pool et al 2023). This study did not evaluate if those Fos-activated neurons were Kp expresing neurons, however, according to our data, those neurons are likely to be Kp neurons due to its close anatomical locations in the precise regions where we report here the presence of kisspeptinergic neurons.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Understanding the complexity of hypothalamic neurocircuits and identifying their molecular signatures is crucial for comprehending the coordinated physiological responses 1 3 . In past years, the high-throughput single-cell RNA sequencing (scRNA-seq) analytical and experimental approaches have facilitated the understanding of the transcriptional cataloging of cell types in the hypothalamus and many other adjacent tissues of the brain 4 6 .…”
Section: Background and Summarymentioning
confidence: 99%